Child‐feeding practices of Indian and Australian‐Indian mothers. Issue 4 (11th September 2014) - Jani, Rati; Mallan, Kimberley M.; Mihrshahi, Seema; Daniels, Lynne A.
Abstract Aim Child‐feeding practices may be modifiable risk factors for childhood obesity; however, investigation of feeding practices in non‐Western populations is scarce. This cross‐sectional study examines the feeding practices of affluent Indian mothers with children aged one to five years residing in Australia and Mumbai, India. The secondary aim was to study the association between maternal and child characteristics and feeding practices. Methods In Australia and Mumbai, 230 and 301 mothers, respectively, completed either a hard copy or online questionnaire. Self‐reported maternal feeding practices (restriction, monitoring, pressure to eat, passive and responsive feeding) were measured using established scales and culturally specific items. Results Mothers in both samples were equally likely to use non‐responsive feeding practices, namely dietary restriction, pressure and passive feeding. Similarly, at least 50% of mothers in both samples did not feed their children responsively (mother decides what and the child decides how much to eat). The only difference observed after controlling for covariates (mothers' age, body mass index (BMI), religion, education, questionnaire type; child's age, birthplace, gender, number of siblings and weight‐for‐age Z‐scores) was that mothers in the Australian sample used higher levels of dietary monitoring (β = 0.2, P = 0.006). Mothers with a higher BMI (OR: 0.84, CI: 0.89–0.99, P = 0.03) and following Hinduism (OR: 0.50, CI: 0.33–0.83, P = 0.008) were less likely to feed responsively. Conclusions These results suggest that Indian mothers in both the samples may benefit from interventions that promote responsive child‐feeding practices.